Desmopressin Effect on Acetylsalicylic Acid Impaired Platelet Punction - Beck, Karl-Heinz; Mohr, Patrick; Bleckmann, Ulrich; Schweer, Hermann; Kretschmer, Volker (Seminars in Thrombosis and Hemostasis, 1995)
The mechanism of DDAVP's shortening of acetylsalicylic acid (ASA) prolonged bleeding times was investigated. Sixteen healthy subjects received two dosages of ASA (100 mg) in 12 hours. Twenty four hours after the first ASA application and again after 32 hours DDAVP was administered intravenously (0.4 μLg/kg). The trial was terminated after 48 hrs. In between, blood samples were drawn and analyzed for the in vivo bleeding time (Simplate® time), in vitro bleeding test (IVBT, Thrombostat 4000), von Willebrand factor antigen (vWf:Ag), Ristocetin cofactor activity (vWf R:Co), plasma β-thromboglobulin (β-TG), platelet ATP/ADP, platelet aggregation (collagen, ADP, arachidonic acid), and plasma and platelet thromboxane levels. Simplate ® time (BT) and IVBT showed an excellent inverse correlation with vWf R:Co (r2BT = 0.97 and r21VBT = 0.99, respectively) during the time when DDAVP was administered, suggesting the involvement of plasma vWF in DDAVP's shortening of the bleeding time. The involvement of plasma thromboxane in this mechanism could be excluded. In addition, DDAVP hampered platelet aggregation tests, possibly due to the inhibition of the release reaction (reduced β-TG in plasma) by a direct interaction with platelets.
Keywords: bleeding time; Thrombostat; acetylsalicylic acid; Desmopressin; thromboxane